2011
DOI: 10.3325/cmj.2011.52.183
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pharmaceutical pricing and reimbursement policies in Croatia to the European Union Member States

Abstract: AimTo perform a comparative analysis of the pharmaceutical pricing and reimbursement systems in Croatia and the 27 European Union (EU) Member States.MethodsKnowledge about the pharmaceutical systems in Croatia and the 27 EU Member States was acquired by literature review and primary research with stakeholders.ResultsPharmaceutical prices are controlled at all levels in Croatia, which is also the case in 21 EU Member States. Like many EU countries, Croatia also applies external price referencing, ie, compares p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 30 publications
(41 reference statements)
0
56
0
2
Order By: Relevance
“…When comparing pharmaceutical expenditure between countries, we strongly advise checking whether data are indicated net or gross. [29,30]) ask the patient to co-pay a specifi c percentage of the medicine price: specifi c medicines, whose therapeutic (added) value was assessed to be lower compared with essential or life-saving medicines, are not fully funded by the public payers, but they are reimbursed to a specifi c extent. For instance, if the pharmacy retail price is Euros 100 and the reimbursement rate is 80%, then the reimbursement price amounts to Euros 80.…”
Section: Price Components and Policies Offi Cial Out-patient Price Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing pharmaceutical expenditure between countries, we strongly advise checking whether data are indicated net or gross. [29,30]) ask the patient to co-pay a specifi c percentage of the medicine price: specifi c medicines, whose therapeutic (added) value was assessed to be lower compared with essential or life-saving medicines, are not fully funded by the public payers, but they are reimbursed to a specifi c extent. For instance, if the pharmacy retail price is Euros 100 and the reimbursement rate is 80%, then the reimbursement price amounts to Euros 80.…”
Section: Price Components and Policies Offi Cial Out-patient Price Typesmentioning
confidence: 99%
“…Pharmacy remuneration may also be designed independently from the price, e.g. by providing a fee for service, such as in The Netherlands or in the UK [1,3,[28][29][30].…”
Section: Price Components and Policies Offi Cial Out-patient Price Typesmentioning
confidence: 99%
“…Cijena novoga istovrsnog lijeka istoga nezaštićenog imena ne smije prelaziti razinu od 90% cijene lijeka (Hrvatski zavod Unazad nekoliko godina postignut je značajan uspjeh u reformiranju politike lijekova koji je rezultirao uštedama u izdacima za lijekove. Uz praćenje i analizu izdataka za lijekove, potrebno je pratiti potrošnju lijekova, razvoj politika za po-ticanje racionalnog izdavanja lijekova, kao i bolnički farmaceutski sektor kako bi se mogao procijeniti utjecaj politike lijekova na cjelokupni sektor zdravstva (Vogler, Habl, Bogut, Vončina, 2011).…”
unclassified
“…With regard to costs, the Association of the European SelfMedication Industry reported that sales of non-prescribed cough and cold products in the European Union increased from 2009 to 2011, constituting €4.8 billion in 2011. 11 Furthermore, in many European countries, health services or insurance companies pay for prescribed medication, 12 resulting in increased costs for these organisations and the societies they serve.…”
Section: Introductionmentioning
confidence: 99%